Ezafe (Genitive) in Zaza Language - Arslan, İlyas (My University, 2022)
Ezafe, which is known as Genitive in European languages and used in Turki, Iranian and Sami languages spoken in the Middle East, is used to link two syntactic elements. Generally, one of the elements is the possessor and the other one is the modifier. There are grammatical elements that link these syntactic structures which at least consist of two units. The historical development of these elements, which varies according to languages, in Iranian languages did not follow the same process. While the languages classified in Northwest Iranian languages, such as Zazaki, varies with a nominal construction, , there are some similarities with Zazaki in the languages belonging to the Southwest Iranian languages group. The purpose of this article is to explore the structures of the nominal phrase in Zaza Language. Both noun and adjective phrases will be analyzed in detail, and other nominal phrases will also be scrutinized. It will also be examined whether these syntactic structures have semantic functions. The origin of Ezafe will be traced back to the Old Iranian languages, and its structure in the Modern Iranian languages will also be investigated. The similarities and differences will be discussed by comparing the functioning of the Zaza language with other Iranian languages. In addition, the nominal phrase constructions in many Zaza dialects will be examined, and it will be investigated whether there are differences between them.